Model of the Effectiveness of Using Tactical Telecommunication Detection Systems in Anticipating the Development of Terrorism by Satintelkam Police Karawang - Aprilianto Pratama Putra (Indonesian Journal of Police Studies, 2024)
This thesis aims to the describe the effectiveness of using tactical telecommunications detection system model in anticipating terrorism development. The problem discussed in this thesis is how the effectiveness of using tactical telecommunications monitoring system model in anticipating terrorism development. To achieve the research objectives, the researcher used some the theories and concepts. They were information technology theory, management theory, effectiveness concept, intelijen concept, the effectivity of using tactical telecommunications monitoring system model concept and terrorism concept. This thesis used qualitative approach and did the field research method in Karawang area. The data in this research was done by observing in the field, interviewing the speakers, and documenting the research results. Based on the findings of research and analysis conducted, it is known that the use of tactical telecommunications monitoring systems is very helpful in anticipating the development of Terrorism. In the implementation, there were stil some obstacles in using the tool which are seen from 4 indicators: man, money, materials, methods, machines. The conclusion in this thesis showed that the stages of the use of tactical telecommunications monitoring systems are very helpful to the Karawang police unit in anticipating the development of terrorism. However, in its implementation several obstacles were encountered that could affect the use of the system.